THE INFLUENCE OF FINANCIAL LITERACY ON THE DIGITAL FINANCIAL INCLUSION OF MSMES IN THE CITY OF BINJAI - Sakti Putra Harahap, Raja; Asmuni, Asmuni; Soemitra, Andri (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the effect of financial literacy on digital financial inclusion for MSMEs in Binjai City. The City of Binjai is a city engaged in services and SMEs. There are only a few natural resources in the City of Binjai. But human resources can be expected for the progress of the City of Binjai. The problem is that many MSMEs do not understand financial literacy well, as a result many MSMEs have gone out of business and are unable to manage their business properly. MSMEs in Binjai City have not exploited digital financial inclusion, some of them are worried about the security of digital transactions, have not experienced the convenience and benefits of managing finances in the digital era, there are still many MSMEs who are concerned about the halalness of financial products and services, as well as cultural factors and refuse understanding new. The formulation of the problem in this study is whether financial literacy affects digital financial inclusion for MSMEs in Binjai City. This research uses a quantitative research method, using primary data sources. Data collection uses a questionnaire. The results of this study are that there is a positive and significant influence on the study entitled "The Influence of Financial Literacy on MSME Digital Financial Inclusion in Binjai City". So it can be concluded that this can be seen from the results of the t test above the tcount value of 4.373 and ttable 1.68195 with a significant level of 0.00 0.05. Because the significant level is greater than 0.05 and t count t table (v 1.68195) which means Ho1 is rejected and Ha1 is accepted, the financial literacy variable has a significant effect on the dependent variable digital financial inclusion. the coefficient of determination R Square is 0.623, which means that the effect of financial literacy on digital financial inclusion is 62.3% and the rest (100-62.3 = 37.7%) is influenced by other variables unknown to researchers.